The Implementasi Media LiGaBil Guna Meningkatkan Pemahaman Konsep Bilangan Bulat Siswa Kelas VI SDN 1 Cibenda - Rohmah; Joko suprapmanto (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
This research was motivated by students' weak understanding of the concept of integers. To increase understanding of a concept, in order to be more optimal and obtain learning outcomes that are in line with learning objectives, it is necessary to use supporting facilities that match the characteristics of the subject and student characteristics, one of which is the use of learning media. The Number Line String (LiGaBil) learning media which is packaged in such a way aims to help improve students' understanding in solving integer arithmetic operation problems, using quantitative descriptive methods. The results of this research indicate that the implementation of LiGaBil media can significantly improve students' understanding and learning outcomes in the concept of integers. Before implementing LigaBil media, 28.89% of students had completed it and after LiGaBil media was implemented consecutively in two cycles, this increased to 86.67%, exceeding the specified target, namely if 80% of students completed the total number of students then learning the concept of numbers The round is complete, although there is still a slight drawback, namely the strength of the medium, especially the numbers made of paper, which come off easily. In the future, it will be further optimized so that it can be used repeatedly. Based on this report, learning media has a very big influence on student learning success. The use of learning media is not only in mathematics subjects, but in all subjects media is very necessary.